The Influence of Digital Social Capital, Self-Efficacy, and Human Capital on Career Success in Fresh Graduate Students in Surabaya - M. Rizal Ariyono Putra; Muhammad Fajar Wahyudi Rahman; Ika Diyah Candra Arifah; Hujjatullah Fazlurrahman (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study seeks to examine the effects of Digital Social Capital, Self-Efficacy, and Human Capital on Career Success among fresh graduates in Surabaya. The research is motivated by the high level of educated unemployment and the intense competition within the urban labor market in the digital era. Employing a quantitative explanatory research approach, the study involved 60 respondents who were graduates of the Bachelor of Management and Bachelor of Digital Business programs at Universitas Negeri Surabaya. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that all three independent variables exert a positive and significant influence on Career Success. Among them, Human Capital shows the strongest effect (β = 0.403; p < 0.001), followed by Self-Efficacy (β = 0.285; p = 0.011) and Digital Social Capital (β = 0.216; p = 0.048). These results indicate that the integration of human capital, psychological resources, and digital social capital plays a crucial role in determining career success among young individuals in the era of digital transformation. Furthermore, this study contributes to theoretical development by integrating Social Cognitive Career Theory and Human Capital Theory, while also providing practical implications for higher education institutions to enhance students’ career readiness through the development of digital competencies, self-efficacy, and professional experience.